PENGARUH VARIASI PEREKAT TERHADAP KARAKTERISTIK BAHAN BAKAR BRIKET CANGKANG KELAPA SAWIT - Alfian, Devia Gahana Cindi; Juhensen, Jodi; Paundra, Fajar; Silitonga, Dicky Januarizky (P3M Politeknik Negeri Indramayu, 2025)
This study explores the utilization of Renewable Energy Sources (RES) through the production of biomass briquettes using palm kernel shells as a sustainable energy source. The raw materials include palm kernel shells as the main component, along with tapioca flour, sago flour, and molasses as binders. The production process involves molding under a pressure of 50 kg/cm² and drying at 100°C for 3 hours. Experiments were conducted with variations in the proportions of the main material and binders, resulting in an optimal composition of 75% palm kernel shells and 25% binder. Test results indicate that briquettes with tapioca flour as a binder exhibit the best characteristics, with a moisture content of 3.74%, a calorific value of 5,405.67 cal/g, ash content of 5.77%, fixed carbon of 56.42%, volatile matter of 44.63%, and a burning rate of 0.1939 g/min. This study validates that the developed briquette formulation meets the SNI 01-6235-2000 standard, demonstrating its potential as a sustainable alternative energy source.